2011
DOI: 10.1002/pbc.23161
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal adenocarcinoma: A rare second malignancy in long term retinoblastoma survivors

Abstract: Retinoblastoma is the most common primary cancer of the eye in children. The incidence of second tumors in survivors of bilateral retinoblastoma and in survivors of unilateral retinoblastoma who presumably carry a germline RB1 mutation is documented. This paper describes the previously unrecognized association of sinonasal adenocarcinoma as a second malignancy in retinoblastoma survivors. We present three cases who received radiation therapy as a part of their treatment and developed sinonasal adenocarcinoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Physici ans should realise that otherw ise innocen t sympt oms, such as a combination of chronic headache and sinus sympt oms, may be potentially indica tive for cranio-facial SPTs. 8 These (chronic) sympt oms in irradiat ed hereditary Rb-pa tients should alert physici ans to perform imag ing without delay in order to detect SPTs at a potentiall y curative stage .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physici ans should realise that otherw ise innocen t sympt oms, such as a combination of chronic headache and sinus sympt oms, may be potentially indica tive for cranio-facial SPTs. 8 These (chronic) sympt oms in irradiat ed hereditary Rb-pa tients should alert physici ans to perform imag ing without delay in order to detect SPTs at a potentiall y curative stage .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The incide nce of SPTs in hereditary Rb is 8.4% at 18-yea rs and 36% at 50-yea rs after diagn osis. 3,4,[6][7][8][9] External beam radiotherap y (EBRT) increa ses the risk for subsequen t malignant neo plasms, as up to 70% of SPTs in Rb patients develop insi de or at bounda ries of the irradiat ion field. 3,4,6,[10][11][12][13][14] The age of Rb-diagnosis and subsequent ly age of irra diation is an addition al risk facto r: patien ts irradiat ed during the first year oftheir-l ife develop two to eight times more SPTs than patien ts irradiat ed after one year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no current therapies that specifically target a unique molecular defect intrinsic to retinoblastoma. The non-specific radio-and chemotherapy treatments can have side effects including cognitive decline and secondary malignancy, which is especially worrisome in such a young susceptible patient population (5)(6)(7). Approximately 1% of patients with retinoblastoma in both eyes develop second non-ocular tumors each year and the cumulative probability of death from these secondary malignancies is 26% at 40 years after diagnosis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Previous studies have demonstrated an increased risk of subsequent central nervous system neoplasms following cranial irradiation, 8,9 and there are several reported instances of sinonasal neoplasm development following delivery of RT adjacent to the brain, such as for retinoblastoma in children. [10][11][12] Tumors of the nasal cavity and paranasal sinuses (sinonasal tumors) are a relatively rare entity, constituting < 5% of all head and neck neoplasms. 13 They have an incidence of < 1 in 100,000 in the United States.…”
Section: Introductionmentioning
confidence: 99%